Histologic Evaluation of Healing Lip Defects Treated With Injected Onabotulinum Toxin A and Topical Mitomycin C. Issue 8 (November 2019) - Jahanbin, Arezoo; Namdar, Parastoo; Ghazi, Narges; Kazemian, Mozhgan
Abstract : Objective: Using an experimental rat model, the efficacy of injected Onabotulinum Toxin A (BoNT-A) versus topical Mitomycin C in surgical wound healing of rat lip defects was evaluated. Methods and Materials: Sixty-seven male Wister rats received a triangular cut (7 × 7 × 4 mm) on their upper lip. Then they were divided randomly into 4 equal groups: group A (topical Mitomycin C plus injected BoNT-A); group B (topical Mitomycin C); group C or control group (saline solution) and group D (injected (BoNT-A). After 3 months, the animals were euthanized and scars were evaluated using hematoxylin and eosin and Masson's trichrome. For qualitative analysis, inflammatory cell density, new capillary formation, fibroblast proliferation, and collagen deposition were reported using relative ranks from 0 to 3 (absence, mild, moderate, marked). Data were analyzed by post hoc and Kruskal–Wallis tests. The significance level was P  < 0.05. Result: Mean collagen deposition values and fibroblast proliferation in the 4 groups showed statistically significant differences with each other ( P value < 0.001). A significant difference between group A and controls existed for fibroblast proliferation (median 1 versus 2, P value < 0.001); also, collagen deposition (median 1 versus 2, P value < 0.001). A significant difference existed between the control and group D (median 2 versus 1, P value = 0.004); also, group A and B (median 1 versus 2, P value = 0.002) for collagen deposition. However, no significant differences existed between the 4 groups regarding inflammatory cells and angiogenesis ( P value > 0.05). Conclusion: Local injection of BoNT-A plus Mitomycin C followed by BoNT-A alone provided less collagen formation and fibroblastic proliferation in the healing lip defect in a rat model. Abstract : Supplemental Digital Content is available in the text